Les "facilitateurs" en droit de la concurrence de l'Union européenne - Labucka Ingrida (Szegedi Tudományegyetem Állam- és Jogtudományi Kar Szeged, 2016)
EU Competition law has recently welcomed a new type of infringement under Article 101 TFEU: a company which provides material or human resources, with the view to offer technical assistance to a cartel, may be fined for its involvement as a “facilitator”. This interpretation of Article 101 TFEU has emerged following two landmark cases which will be reviewed in this contribution: AC-Treuhand I and AC-Treuhand II, in which the EU judges agreed on an extensive interpretation of the terms “agreement” and “undertaking” included in Article 101 TFEU, in order to encompass companies which are not active in the cartelized market. In the present author’s view, this new reading of Article 101 TFEU will allow to fine companies which are engaged in morally blameworthy behaviors in the market, thus preserving the effectiveness of the EU Competition law.
Keywords: Társadalomtudományok; Jogtudomány